Anatomic diagnosis: a defense - Combs, Sunset, author; Fletcher, Harrison, advisor; McConigley, Nina, committee member; Souza, Caridad, committee member (Colorado State University. Libraries, 2023)
This collection of letters in the form of a defense looks to showcase poor white womanhood and the expectations for violence that are inherent in the systems that teach and protect them. Using personal experience, archival documents, and cultural critique Anatomic Diagnosis: A Defense questions the ways we can reenact the violence that has been to us. Looking specifically at the academy and state-run institutions, this collection exposes the possibility of exploitation when personal trauma becomes a commodity in a capitalist system. It uses the lives of three generations of women who have worked to barely live and learned to make a home out of the injustice that was their everyday reality.